Distortions of ethyne when complexed with a cuprous or argentous halide: the rotational spectrum of C2H2⋯CuF1. Issue 29 (7th August 2015) - Zaleski, Daniel P.; Stephens, Susanna L.; Tew, David P.; Bittner, Dror M.; Walker, Nicholas R.; Legon, Anthony C.
<x xml:space="preserve">Abstract</x> A new molecule C2H2⋯CuF has been synthesized in the gas phase by means of the reaction of laser-ablated metallic copper with a pulse of gas consisting of a dilute mixture of ethyne and sulfur hexafluoride in argon.